Peran Dukungan Keluarga dalam Melakukan Pemeriksaan Payudara Klinis pada Wanita - Laili, Fitria Jannatul; Claudia, Jessica; Nisa, Khoirun (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
Many clients (Women of Reproductive Age/WUS) are reluctant to do a clinical breast examination (SADARNIS). Clients feel embarrassed and worried if a disease is found or diagnosed with a certain disease. There are some WUS who think that they don't feel any complaints about their breasts so they feel they don't need routine breast examinations. Even though early detection and prevention of morbidity and mortality due to breast cancer is very important. Breast cancer can be detected independently by routine breast self-examination (BSE) and awareness. If a woman has breast cancer who previously did not do BSE or BSE regularly, she is likely to come to a health facility in a severe condition. Therefore, it is necessary to support women to be confident so they want to do awareness routinely. This support is mainly from the husband and/or family. The role of the husband or family has proven to be effective in providing opportunities for women to be aware of routinely. Keywords: Family Role, Breast Examination